Analysis on Sealing Performance for a New Type of Rubber Olecranon-Shaped Sealing Ring in Pipe Jacking Joint - Yi Zhang; Zaiqian Chen; Duoxian Wu; Hao Yan; Qiao He; Lei Wang (Advances in Civil Engineering)
To address the easy damage of rubber sealing rings for pipe joints used in China’s first rock pipe jacking project, the launch of research concerning the optimization design of rubber ring structure was decided. However, modification based on the existing production mold was required, to prevent the construction period and cost from exceeding limits. Utilizing the optimization experience, the stress and waterproof property variations of rubber ring before and after optimization during the pipe translation and deflection were initially analyzed via the ADINA software. Meanwhile, the correct orientation of the ring optimization criteria was confirmed through the field test. Next, the effects of key structural parameters on the contact length and maximum contact pressure of rubber ring were quantified, thereby obtaining the sensitivity correlations between five key parameters of ring optimization to further establish the criteria for rubber ring optimization. The findings of this study offer safe construction suggestions for pipe jacking projects.